Factors Affecting MSMEs Taxpayer Compliance with Taxpayer Knowledge as Moderating Variables - Anissa, Anissa Yuniar Larasati; Bani Binekas (International Journal of Educational Research & Social Sciences, 2021)
Taxes are the largest source of revenue in Indonesia. In recent years MSMEs have made a good contribution to the economy in Indonesia. This is the focus of the government to explore the potential for taxes contained in MSMEs. The purpose of this study is to determine the factors that influence taxpayers with tax knowledge as a moderator variable. There are four independent variables tested, namely the tax awareness factor, tax attitudes factor, rational attitude factor, and tax law factors, and the tax knowledge variable being the moderating variable. While the dependent variable is the MSME taxpayer. The sampling method used was a purposive sample with a sample size of 100 UMKM taxpayers. This research uses the Moderated Regression Analysis (MRA) equation model with the help of SPSS v.21. This research method is quantitative, namely searching for data primarily with the research object of MSME taxpayers who are registered in the SME cooperative trade service and industry in the city of Cimahi. Based on the partial research, the variables that have a significant effect are the awareness factor, the tax officer factor, and the rational factor, while the tax law factor does not have a significant effect. While tax knowledge is tested as a moderating variable, tax knowledge has an effect that affects tax awareness and reduces rational factors. Meanwhile, the tax officer and tax law variables have a moderating effect.